Chivalry in Late Medieval Tuscany and Florence: Current historiography and new perspectives - Sposato, Peter (History compass, 2018)
Chivalry was the dominant ethos of the lay elite in high and late medieval Europe, including in Italy. Chivalric ideology helped to shape the mentality, lifestyle, and identity of nobles, knights, and men-at-arms and to reinforce their claims to social, political, and economic superiority. While scholars have spilled considerable ink studying chivalry's powerful influence in northwestern Europe, especially in England and France, there has been far less interest in the topic among historians of Italy. This article will examine the existing historiography on chivalry in one region of the peninsula, Tuscany, with a particular focus on the city of Florence. The traditional interpretation of chivalry found in these works is that of an ideology predominantly courtly and ceremonial in nature. This article will also introduce the newest scholarship which challenges this conceptualization of Tuscan and Florentine chivalry and offers a new interpretation that is in line with the most recent studies of chivalry in the general European context.